Refractive Index Sensor Based on Spiral-Shaped Plastic Optical Fiber - Tiwari S.; Singh M.K.; Pandey P.C. (My University, 2025)
A spiral shaped plastic optical fiber (POF) has been constructed and applied for sensing of the refractive index of a sucrose solution. The sensing mechanism is based on evanescent wave interaction between the light travelling within the fiber and the medium surrounding it. Difference in output voltage is observed as the concentration of sucrose solution is varied from 10% to 50%, demonstrating a uniform relation among them. By varying the pitch of the spiral shape and applying strain to the same, the sensitivity of the POF is refined. This spiral-shaped POF sensor is comparatively easy to fabricate, has low cost of operation, and provides real-time sensing-based data. © 2016 IEEE.